PENERAPAN ALGORITMA RSA UNTUK KEAMANAN PESAN INSTAN PADA PERANGKAT ANDROID - Muhammad Arif Zaenuddin; Dadang Iskandar Mulyana (CKI ON SPOT, 2016)
This time the use of smart phone is very popular among every circle of society, especially Android base device. Start form low end society to mid high society are so familiar with Android base smartphone. One of feature that is use by many Android users is Instant Messenger. Instant Messenger is favored because it speed to transmit message and cost that relatively low, it count base on size of data that transmitted. As many user that use this service secrecy feature to ensure safety of text that is send is became main attention of users. Cryptography is one solution that can be use and develop to keep secrecy of instant messenger. With encryption, secrecy and safety of text can be made.  Cryptography have many technique to do encryption of text or message, one of those technique that have high security and hard to decode is RSA algorithm. Implementation of RSA algorithm to Instant Messenger application is to encrypt message using public key before message is transmit. On receiver side using private key that generated to decrypt received message. Purpose of this this is to make sure message can only be read by intended receiver. If message is receive by unintended receiver then send information will be hard to understand, because message that is received only show number of codes that hard to described. Message that is send is receive by server application and be continued to intended receiver.Keywords: Android, Instant Messenger, RSA